GHINS, Michel. Scientific Realism and Laws of Nature: A Metaphysics of Causal Powers. (Springer, 2024, xviii + 211 pp.) - Deiver de Melo (Manuscrito)
Abstract This is a critical analysis of Scientific Realism and Laws of Nature: A Metaphysics of Causal Powers, by Michel Ghins.